Assessment of productivity perceptions and factors for Vietnamese construction personnel - Do Thi Xuan Lan; Chotchai Charoenngam; Baba, Keizo; Do Ba Khang; ADB Japan (Bangkok : Asian Institute of Technology, 1997)
Being an initial swvey of the considerations for productivity improvement within the Vietnamese building construction, this research assesses construction people's awareness about productivity issues as well as evaluates imp01tance level of major on-site productivity factors via engineer questionnaire smvey and worker inte1view swvey, and determines how the working day is utilized by construction workers by work sampling technique. Although most of construction people agree with the fact that productivity has been improved significantly in the construction industry recently, their perceptions towards other productivity issues are diverse. Therefore, there is a need for managers to make an effort to improve their employees' awareness towards productivity issues. The highest ranking factors impairing productivity are "material unavailability", "financial sh01tages", "poor workers' skills" and "inefficient equipment utilization". The smvey indicates that workers' job satisfaction is rather low while lower level needs of construction workers are not well satisfied at this time. Work sampling results show that on average, workers spend 32%, 37% and 31 % their working day on productive, supp01tive and unproductive works, respectively.
Thesis (M. Eng.) - Asian Institute of Technology, 1997
A thesis submitted in pa1tial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Keywords: Construction workers -- Vietnam